Pengaruh Edukasi Kesehatan Mental Emosional terhadap Status Mental Emosional Remaja di SMPN 4 Banyuwangi - Efendi, Achmad; Setiawati, Ananda; Soekardjo; Al Amin, Muhammad; Anitarini, Fany (Jurnal Keperawatan Muhammadiyah, 2025)
ABSTRACT Objective: Mental emotional health issues in adolescents often stem from imperfect self-control due to mood fluctuations and stress during this developmental phase. This study aims to assess the impact of mental emotional health education on adolescents' mental emotional status. Methods: Utilizing a quantitative approach with a True Experimental method, specifically a Pre-Post Control Group Design with Randomized Controlled Trials (RCT), the research involved adolescents from SMPN 4 Banyuwangi. The sample comprised 28 respondents in the experimental group receiving mental emotional health education and 28 in the control group receiving conventional education. Resukts: Results indicated a significant improvement in mental emotional status post-intervention. T-test analysis revealed p=0.039 for the experimental group and p=0.020 for the control group, leading to the acceptance of the alternative hypothesis (Ha). This suggests that mental emotional health education is more effective in enhancing mental emotional status compared to conventional education. Conclusion: The findings underscore the importance of raising awareness about mental emotional health and implementing strategies to address related issues, highlighting the necessity of maintaining mental well-being among adolescents. This study advocates for increased focus on mental emotional health education to better equip adolescents in managing their mental health challenges.